The Relationship Between Family Support And Levels of Depression In Patients With Chronic Kidney Disease Who Undergo Hemodialysis Therapy in RSUP Sanglah Hospital Denpasar - Ni Ayu Rantini Indrayani (Coping: Community of Publishing in Nursing, 2013)
Depression is described as a mental health disorder that most commonly occurs in patients receiving chronic dialysis therapy. Dependent conditions over hemodialysis treatment leads to changes in the lives of people with kidney disease that can create conflict, frustration, the feeling of guilty and depression in the patient and family. Family support as one of the depression treatments can be a motivation for the care and treatment of patients. Family support can be provided through emotional support, information or advice, instrument and appreciation. Support both physically and psychologically from the closes person or family in particular, can increase a person's coping in the face to confront a stressor. This study aims to determine the relationship between family support and the level of depression in patients with chronic kidney disease undergoing hemodialysis therapy in RSUP Sanglah Hospital Denpasar. This study is a correlational study with a cross sectional approach. The sample consisted of 75 patients with chronic kidney disease (CKD) undergoing hemodialysis therapy (HD) is selected by consecutive sampling. Data is collected using questionnaire guide of family support and depression BDI-II questionnaire. The results obtained r value is -0.308 and the Sig. (2-tailed) of 0.007 p <? (0.05), which means there is a significant relationship between family support and level of depression in patiens with chronic kidney disease undergoing hemodialysis therapy in RSUP Sanglah Hospital Denpasar.